Can the studies at a spatial scale of 100s meters detect the spatiotemporal fluctuations of a parasite assemblage? - Parietti, Manuela (2013)
The importance of small-scale heterogeneity in local factors which overrides that of larger-scales factors, suggest that local factors play a major role in determining the richness and prevalence of larval digeneans in intertidal gastropods. The restricted distribution of the snail Heleobia australis along a 500 m transect in Cangrejo creek (Mar Chiquita, Argentina) provides a good opportunity to test the assumption that a study at spatial scale of 100s meters can detect spatiotemporal fluctuations of a larval digenean assemblage. To analyze that, 3600 specimens of H. australis were collected seasonally during the year 2011. A quantitative variation and a space-time interaction between sampling points and seasons of the year for the total prevalence of larval digeneans and snail’s densities were found, as well as a positive correlation with abiotic factors. These results revealed that the fluctuations in the community of larval digeneans of the snail H. australis can be detected at small spatial scale, using its natural distribution of 500 m. This study also highlights the importance of seasonality as a factor that must be considered in studies focused on the search for patterns structuring the communities of larval digeneans, at medium and large scales.